2017
DOI: 10.1016/j.commatsci.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Beat phenomenon in metal nanowires: A molecular dynamics study

Abstract: In this paper, a special beat phenomenon of metal nanowires is investigated by using the large scale molecular dynamics simulations. It is observed that the beat phenomenon exists not only in the vibration of <110> orientated Face Center Cubic (FCC) nanowires of different materials, but also in the vibration of <100> orientated Body Center Cubic (BCC) nanowires.Based on the atomic arrangement, a discrete spring-mass model is developed to explain the displacement characteristics of nanowire's vibration. It is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In molecular dynamics (MD) simulations context, some res earchers [119,[362][363][364][365][366] showed that beat phenomenon (or the flexural mode doublets) in nanowire (NW) resonators not only may originate from the geometrical asymmetries but also from the asymmetric lattice arrangements in lateral directions. They found that the dual orthogonal flexural mode can be effectively tuned by selecting the proper growth direction in NWs, which creates two different principal moments of inertia.…”
Section: Linear Modal Coupling: Single Resonatorsmentioning
confidence: 99%
“…In molecular dynamics (MD) simulations context, some res earchers [119,[362][363][364][365][366] showed that beat phenomenon (or the flexural mode doublets) in nanowire (NW) resonators not only may originate from the geometrical asymmetries but also from the asymmetric lattice arrangements in lateral directions. They found that the dual orthogonal flexural mode can be effectively tuned by selecting the proper growth direction in NWs, which creates two different principal moments of inertia.…”
Section: Linear Modal Coupling: Single Resonatorsmentioning
confidence: 99%
“…Conley et al have studied it theoretically [14] and Gil-Santos et al have used it for mass sensing and stiffness spectroscopy [6]. In the nanowire's two-dimensional vibration, beat phenomenon is a special physical characteristic, which was reported and investigated recently [21,22,31,32]. However, little attention has been paid to another tough and useful problem -the nonlinear vibration behaviors of nanowires, especially the Fe nanowires.…”
Section: Introductionmentioning
confidence: 99%